Website sobre Síndrome de Down e a internet como fonte de informação em saúde - Oliveira, Fábio de (2013)
Introduction: The digital media revolution has made information technology accessible to a great number of users. However, the content in health, in general, is available to the public based on their own experiences and without scientific background. Due to this picture, the Ding Down team, a multidisciplinary group of professionals from a teaching medical school, has been providing care for individuals with Down syndrome (DS). They sought the need to create a Website to spread accurate, scientific quality, following the codes of conduct of healthcare based on the Health On Net foundation (HON) and standardizations from the Institute of Health Information Technology - (HiTi). DS is the most common cause of mental disorder from genetic etiology, characterized by the presence of three copies of chromosome 21. Its prevalence is approximately 1:660 births, and an outcome of great social impact. Objectives: To Develop website and forum in DS and present the importance of the internet as a source of health information. Materials and Methods: For Website construction, the development platform and manageability Joomla and PHP, and Web Server as the APACHE. The operating system used was Linux Mandriva and software was: NVU14, editing HTML and PHP, 15 GIMP image editing and documentation for BrOffice. The above considerations about the importance of the Internet in health were based on available studies based on sites with content, books, papers, theses or dissertations submitted in English or Portuguese language, in full version. Studies published between 1995 to 2012 were selected through an electronic search on Science Direct, Medline / Pubmed, Lilacs, SciELO, Biomed Central and PsycInfo using the following keywords: Health or Health and internet, combined with Internet History, quality of Health in the Internet. Results: The website domain was hosted in the Intelig' Data Center and was defined as http://www.dingdown.com.br and was well accepted by health professionals and the community. Statistical data showed that, by the end of August 2012 was hit a total of 6964 visitors surpassing the full year 2011, with 2396 visitors. Regarding to health information on the Internet there was a growing number of scientific journals in this area and most are available online, of which 20 000 are in the field of Medicine. Above all, there is a huge number of websites that are not certified. Conclusion: The access to content based on information with credibility and scientific support could provide knowledge by clarifying about DS. The Internet is an important device to spread healthcare knowledge, however, it is important the authorities should regulate the quality of health information. The result would provide reliability for users who are not able to differentiate the credibility content from those presented in some portals without scientific support.